Accuracy of age-adjusted D-dimer to rule out deep vein thrombosis in the elderly. Issue 174 (February 2019) - Riva, Nicoletta; Righini, Marc; Camporese, Giuseppe; Iotti, Matteo; Bucherini, Eugenio; Kamphuisen, Pieter W.; Verhamme, Peter; Douketis, James D.; Tonello, Chiara; Prandoni, Paolo; Ageno, Walter; ,
Highlights: The PALLADIO algorithm combined PTP with DD to drive the use of CUS in patients with suspected DVT. The use of age-adjusted DD cut-offs has been recently proposed to increase DD specificity. The age-adjusted DD in elderly outpatients with unlikely PTP reduced the need of CUS by almost 9%. No symptomatic VTE during the 3-month follow-up occurred in this group of patients.